Acoustic response behavior of porous 3D graphene foam plate. (1st December 2020) - Kumar, Ashish; Gunasekaran, Vijay; Chinnapandi, Lenin babu Mailan; Pitchaimani, Jeyaraj
Highlights: Plate with more porosity around the center and less porosity at the outer surfaces has high natural frequency. Sound power radiated is controlled by both the nature of porosity distribution pattern and porosity coefficient. STL of the plate with less porosity around the center and high porosity at the extreme surface is high. Abstract: Sound radiation and sound transmission loss (STL) behavior of porous 3D graphene (3D-GrF) foam plate are presented. Two variable refined plate theory which includes both transverse bending and shear stresses is used to model the plate and Navier's solution is used to calculate the vibration responses while Rayleigh integral is used to analyze the acoustic response. Variation in free vibration frequencies with the nature of porosity distribution is significant for the 3D-GrF plates having higher porosity co-efficient. The natural frequency of the 3D-GrF plate with more porosity around the center and less porosity at the outer surfaces is high. However, resonant amplitudes of the responses and STL of the plates are controlled by both the nature of the porosity distribution pattern and porosity co-efficient. In general, STL of the plate with less porosity around the center and high porosity at the extreme surfaces is high compared to the other cases.